Properties Controlling Phosphorus Adsorption and Stability in Amazonian Agro-Industrial Waste Biochars: a Multivariate Approach - Canteral, Kleve Freddy Ferreira [UNESP]; Dias, Yan Nunes; Fernandes, Antonio Rodrigues (Springer Nature, 2023)
The application of biochar from agro-industrial residues of the Amazon is a key strategy to optimize the use of phosphorus (P) in agriculture and provide the proper management of these materials. In this study, we investigated the relationship between the chemical constituents of biochars from açaí seeds (BA), Brazil nut shells (BN) and palm kernel cake (BK) with phosphorus adsorption to identify the main properties that control this process and the thermochemical stability of carbon (C). Biochars were produced under slow pyrolysis (3.33 ºC min–1) at 700 ºC and evaluated regarding their physicochemical properties, elemental composition and maximum P adsorption capacity (qm). The interrelationship between the properties of the biochars was described by multivariate techniques: factor analysis (FA), canonical correlation analysis (CCA) and hierarchical cluster analysis. The multivariate approach allowed the analysis of the properties of biochars associated with qm and provided the differentiation between the biochars derived from different agro-industrial residues. FA and CCA indicated a high association (r ≥ 0.93; p < 0.05) of qm with ash content, cation exchange capacity (CEC) and nitrogen (N) content. Therefore, small increments in these attributes can cause variation in the rate of P adsorption. The heatmap allowed the identification of greater similarities between BA and BN; and greater contrast between qm with the aromaticity indices H/C and O/C and the polarity index (O + N)/C. Our results indicate that these biochars have the potential to adsorb P, increase the thermochemical stability of C in soil and represent a sustainable alternative for waste management of eastern Amazon. Graphical abstract: [Figure not available: see fulltext.].
Keywords: Carbon stability; Environmental contamination; Multivariate techniques; Phosphorus recovery; Waste disposal